Pengaruh Komitmen Organisasi dan Budaya Kerja Terhadap Disiplin Kerja Karyawan - Shakilah Ismayati; Arga Sutrisna; Kusuma Agdhi Rahwana (CV. Ulil Albab Corp, 2022)
This study aims to determine and analyze the effect of organizational commitment and work culture on the employee work discipline (a case study on the polyester section of PT. Bineatama Kayone Lestari). The type of data used in this study using primary data collection methods directly from the object of research. With a sample taken as many 53 employee. In this study using multiple linear regression. Data processing in this study used SPSS version 26. The results showed that: Partially, organizational commitment had no significant effect on employee work discipline. Partially, work culture has a significant effect on employee work discipline, simultaneously, it is known that there is significant influence between organizational commitment and work culture on employee work discipline.